The role of adhesion protein Fibulin7 in development and diseases - Chakraborty, Papiya (Mol Med, 2020)
Fibulins are a family of secreted glycoproteins, which play an important role in regulating multiple cellular functions such as adhesion, growth, motility, and survival. Fibulin7 (Fbln7) is expressed in developing odontoblasts, in the giant trophoblast layer of the placenta, in the choroid of the eyes as well as in the cartilage. Since its discovery, reports from various research groups have improved our understanding about the roles and effects of Fbln7 and Fbln7 derived fragments and peptides under physiological and pathological conditions such as tooth development, angiogenesis, immunoregulation, cancer pathogenesis and very recently as a possible biomarker for glaucoma. This review will highlight the latest developments in our understanding of the functions, the proposed mechanism of actions, and Fbln7’s possible implications in future research and as therapeutics for different diseases.